Liberia Economic Update, June 2020 : The COVID-19 Crisis in Liberia - Projected Impact and Policy Options for a Robust Recovery - World Bank (World Bank, Monrovia, 2020)
When the global COVID-19 (Coronavirus) pandemic emerged in early 2020, Liberia was already facing a challenging domestic and external environment. Weak consumption and declining output had caused the Liberian economy to contract by an estimated 2.3 percent in 2019. Meanwhile, the inflation rate reached 27 percent, eroding consumer purchasing power and undermining household welfare, and fiscal consolidation and monetary tightening further weakened domestic demand during the second half of 2019. However, the economy was poised for a recovery in 2020, underpinned by a positive global and regional outlook, a renewed focus on responsible macroeconomic management, improved governance, and structural reform. The IMF’s Extended Credit Facility (ECF) progra